2015
DOI: 10.1038/srep11247
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a critical determinant that enables efficient fatty acid synthesis in oleaginous fungi

Abstract: Microorganisms are valuable resources for lipid production. What makes one microbe but not the other able to efficiently synthesize and accumulate lipids is poorly understood. In the present study, global gene expression prior to and after the onset of lipogenesis was determined by transcriptomics using the oleaginous fungus Mortierella alpina as a model system. A core of 23 lipogenesis associated genes was identified and their expression patterns shared a high similarity among oleaginous microbes Chlamydomona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
113
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 87 publications
(117 citation statements)
references
References 39 publications
4
113
0
Order By: Relevance
“…Fermentors were held at 28°C and stirred at 500 rpm with an aeration rate of 0.5 vol/vol/min (vvm), and pH was maintained at 6.0. Samples were harvested prior to (sample A, Ϫ12 h; sample B, Ϫ2 h; sample E, Ϫ30 min) and after (sample K, ϩ1 h; sample L, ϩ12 h; sample M, ϩ48 h) nitrogen exhaustion as previously described (1).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Fermentors were held at 28°C and stirred at 500 rpm with an aeration rate of 0.5 vol/vol/min (vvm), and pH was maintained at 6.0. Samples were harvested prior to (sample A, Ϫ12 h; sample B, Ϫ2 h; sample E, Ϫ30 min) and after (sample K, ϩ1 h; sample L, ϩ12 h; sample M, ϩ48 h) nitrogen exhaustion as previously described (1).…”
Section: Methodsmentioning
confidence: 99%
“…ADPH is a critical factor for many biological processes in oleaginous microbes (1,2). However, the function of the various sources of NADPH in fatty acid synthesis is still not fully understood.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Functional study of bovine FADS6 has not been reported, but they were found to be highly similar to human FADS6. The FADS6 gene in humans is homologous to FADS2 (Stroud et al, 2009;Chen et al, 2015). FADS2 synthesizes Delta-6-desaturase (D6D) that catalyzes the first step in the synthesis of highly unsaturated fatty acid (HUFA) or LC-PUFA (Long chain-Poly unsaturated fatty acid (Stroud et al, 2009;Zheng et al, 2004).…”
Section: Genetic Effects On Famentioning
confidence: 99%